Association of single nucleotide polymorphisms of SPAG11 gene with semen quality and testicular traits of boer goats - Harighi, Mohammadfazel (2019)
Goat is a resistant species to Malaysian tropical climate. Boer is a goat’s breed with a large body size that has been imported to Malaysia to improve the small body size of indigenous Katjang population. Since Boer population has become one of the important goat flocks in Malaysia, knowing about its characteristics, especially in connection with reproductive performance is an essential step for goat breeding programs. Bucks reproduction performance plays a key role in flock profitability affecting the number of pregnant does. Moreover, commercial sector is highly interested in identification of the buck fertility variation based on semen quality traits for artificial insemination (AI) purpose. Therefore, applying a proper selection method that is accurate in the selection of high fertile bucks would be a great approach. Conventional selection methods are mostly time-consuming and costly. Besides, they are not proper for early selection purpose. Thus, using the single nucleotide polymorphism (SNP) of particular candidate genes as molecular marker might be an appropriate alternative. Sperm-associated antigen 11 (SPAG11) is known as an important candidate gene that affects the male reproductive performance. The objectives of this study were to find single nucleotide polymorphisms in a fragment of the SPAG11 gene and to determine their associations with semen (both fresh and post-thaw) quality traits including testicular weight (TW), testes dimensions (length, width, and thickness), and testicular volume (TVm) in 52 heads Boer bucks. Semen was collected from each animal using electro-ejaculation (EE). Semen quality traits including sperm viability, morphology, motility, and density were analyzed using both Hemocytometer and light microscope. Semen volume and testes dimensions were measured using a graduated test tube and a dial caliper, respectively. Levelled container was invented as an alternative method to measure TV. Genomic DNA was isolated from blood of each buck. Primers were designed to amplify two exons of the given gene. The SNPs were detected using single-base extension (SBE) method along with molecular cloning technique. Four SNPs were detected in the coding region of exon 1 and 2 of the SPAG11 gene, two of which were synonymous (1264A>G and 1333A>G) and other two namely 1278C>T and 1335G>A were non-synonymous SNPs caused changes in the amino acids Thr>Ile and Arg>Gln, respectively. The results indicated that the levelled container is a valid utility for measuring the testicular volume. There was a negative association between 1335G>A mutation with testicular volume (p = 0.002). Moreover, neither the studied testes dimensions (length, width, and thickness) nor TW were associated with detected SNPs. Although association between 1333A>G SNP and both fresh and post-thaw semen traits were insignificant, still negative effects on studied traits were observed. The SPAG11 gene showed more association with sperm morphological traits rather than semen volume, sperm viability, and sperm density in fresh semen. The 1264A>G loci was negatively associated with sperm abnormality of head (%) trait in fresh (p = 0.042) and post thaw (p = 0.018) semen. The 1335G>A mutation was positively associated with sperm abnormality of head (%) (p = 0.002), mid piece (%) (p = 0.008), tail (%) (p = 0.007), and live sperm (%) (p = 0.001) traits in fresh semen. In conclusion, this study elucidated significant association of SPAG11 gene with sperm quality traits and TV in Boer goat. The detected polymorphisms of this candidate gene can be used as a marker assisted selection (MAS) for improving semen quality traits in the Boer goat populations. The detected SNPs (1264A>G and 1333A>G) that showed a negative association with semen quality traits, especially with both fresh and post thaw, can be considered as a marker for artificial negative selection. The significant association between this candidate gene and TV indicates that TV can be used as a proper trait for pre-selection of fertile Boer goats.